Proximate Composition and Determination of Epigallocatechin Gallate Content in Melon Manis Terengganu - Shahidan, Norshazila; Ong, Ying Qian; Harith, Sakinah; Shahril, Mohd Razif; Hapidin, Hermizi (Halalsphere, 2022)
Melon Manis Terengganu (MMT), Cucumis melo L., is a newly developed variety of melon introduced specifically for Terengganu. MMT has been claimed to have a high antioxidant value. Epigallocatechin gallate (EGCG) has become one of the leading naturally derived polyphenols studied for its potential health benefits. In the present study, the proximate composition and EGCG content of MMT were determined and compared among the fruit parts (flesh, seeds, and peels). The powdered samples have undergone proximate analyses followed by the determination of EGCG concentration using high performance liquid chromatography (HPLC). The result revealed that MMT seed has highest protein (27.99 ± 0.36%), fat (28.79 ± 0.32%) and crude fibre (31.64 ± 1.25%) contents as compared to peel and flesh. MMT peel contained the highest carbohydrate (67.48 ± 0.37%) as compared to flesh and seed. The EGCG concentrations of MMT seed, flesh and peel were significantly different (p < 0.05) among one another with MMT peel as the highest EGCG concentration (0.042 ± 0.003 mg/mL). Therefore, MMT peel has the potential to consider as new sources of natural antioxidants for food and nutraceutical products as it contained the highest EGCG concentration as compared to seed and flesh